ASSESSMENT OF BACTERICIDAL ROLE OF EPIDERMAL MUCUS OF MAJOR CARPS AGAINST PATHOGENIC MICROBIAL STRAINS - Farkhanda Asad; Shahzad Nasir; Itrat Fatima; Zeliha Selamoglu; Aiman Nadeem; Rafia Jamal; Maryam Fatima; Maimoona Mehmood (Science Journal of University of Zakho)
This research evaluated the antimicrobial potential of mucus from major carps, specifically Cirrhinus mrigala and Labeo rohita, against Klebsiella pneumoniae and Escherichia coli. Fish weighing 300-350 grams were stoked and acclimated for 15 days, fed with commercially available diet at 4% of their body weight.  Fish were treated with KMnO4 solution to avoid any infection before mucus collection and collected mucus was stored at 4°C. Mucus extracts were screened for antibacterial potential using the agar well diffusion method, measuring antibacterial effects by the zone of inhibition (ZOI) in mm. L. rohita secreted more mucus than C. mrigala. The mucus appearance of L. rohita was highly viscous, while less viscous in C. mrigala. In L. rohita mucus, maximum antimicrobial efficiency was observed. Results showed greater efficacy in limiting the growth of E. coli with zone of inhibition (16mm). Mucus is a key defense against disease. Fish skin mucus can serve as an alternative to antibiotics for use in aquaculture and potentially for human application. As a natural product, it may help reduce problems associated with antibiotic resistance.